Evaluation of Soft Skills Training to Improve Performance Using Interpersonal Skills of MSMEs at Cafana Coffee - Intania Putri Ananda; Marta Widian Sari; Anisa Oktaviani; Nesya Anggraini; Tiara Shandini (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
This community service program (PKM) aims to recognize and increase understanding of the knowledge of owners and employees regarding the evaluation of soft skills training in improving performance using interpersonal skills at Cafana Coffee. The evolution of people's lifestyles and the diversity of consumer needs for something, raises creativity and willingness to provide and fulfill the needs of the coffee-making community that makes it easy for consumers to find a place to relax in the form of a coffee shop. The current economic growth can be seen from consumer interest in coffee shops, which has led to the development of this form of coffee business in an area of their coffee.